Mediating effect of digital marketing capability on marketing effectiveness of community enterprises in Nakhon Pathom Province, Thailand - Niracharapa Tongdhamachart; Sakkarin Niyomsilpa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Most community enterprises in Thailand are not successful because of limited marketing channels and technology. The purpose of this paper is to examine the effect of platform capability and web capability on marketing effectiveness with a consideration of the mediating effect of digital marketing capability to community enterprises in Nakhon Pathom Province, Thailand. The study uses a multi-stage sampling method surveying 400 community enterprise members in Nakhon Pathom Province. The model applies and combines the concepts of dynamic capability. Data analysis uses structural equation modelling and the LISREL program for path analysis and testing the congruence of the causal relationship model. The causal model of factors influencing marketing effectiveness significantly fits the empirical data. The fit statistics are c2= 349.046, df = 245, p-value = 0.158, c2/df = 1.425, RMSEA = 0.024, NFI = 0.996, NNFI = 0.998, CFI = 0.996, RMR = 0.024, SRMR = 0.024, GFI = 0.933 and AGFI = 0.910. The results show that digital marketing is a full mediating effect of platform and web capabilities on marketing effectiveness of community enterprises. Community enterprises need to implement more online marketing channels for better performances. Moreover, the study serves as a guideline for developing community enterprises and the capability level of grassroots, which are a significant base of local economic development of Thailand. Importantly, grassroots development has been a national agenda of the Thai government.